Morpho-physiological and productive biometry in semi-erect cultivars of the cowpea under different plant populations - Bezerra, Antônio Aécio; das Neves, Adão; Rocha, Maurisrael; Brito, Lucélia de Cássia (Revista Ciência Agronômica, 2017)
The aim of this study was to evaluate morpho-physiological and productive characteristics in four semi-erect cultivars of the cowpea under five plant populations. The experiment was conducted in the experimental area of Embrapa Meio-Norte in Teresina in the State of Piauí, Brazil (PI). The experimental design was of randomised complete blocks with four replications, in a 4 x 5 factorial scheme, for evaluating four cultivars (BRS Guariba, BRS Novaera, BRS Potengi and BRS Tumucumaque) and five plant populations (105, 2x105, 3x105, 4x105 and 5x105 plants ha-1). There were significant differences between cultivars for primary branch length (PBL), number of lateral branches (NLB), 100-grain weight (HGW), and dry-grain yield (GY). The maximum PBL of 58.5 cm was obtained with 300 thousand plants ha-1, corresponding to an increase of 11.5% when compared to 100 thousand plants ha-1. However, there was a reduction of 91.2% in NLB when compared to the populations of 100 and 500 thousand plants ha-1. The increases of 188% obtained in the leaf area index (LAI) in the range of 100 to 500 thousand plants ha-1 explain the linear increase in the crop growth rate (CGR) as being due to the greater production of leaf area; also, the decreases seen in the net assimilation rate (NAR), especially in the range of 100 to 300 thousand plants ha-1, are explained as due to the consequent self-shading, which was intensified in the larger populations. LAI, light interception, and CGR in the cultivars increase in response to higher densities. HGW and GY are not significantly affected by the different populations.